Localization of Brutalist Architecture in Post-War Turkey: Three Unique Examples from Istanbul - BALCI ÖZTÜRK Özlem; ŞENYURT Oya (Architecture, Civil Engineering, Environment)
Brutalism, a revision of Modernism, originated in England in the 1950s and spread rapidly globally. This intercontinental expansion has led to distinctive local diversity in different geographies, from Europe to the America. Concurrent with global examples, brutalist buildings began to appear in Turkey in the early 1960s. Notably, in Istanbul, Brutalism has managed to localize and create unique examples. This study investigates the transition of Brutalism between geographies and its localization in Turkish Architecture. This study analyzes brutalist and brutalist-influenced structures in Istanbul. According to the results of this analysis, the unique examples of Manifaturacılar Retail Center, Istanbul Reklam Building, and Istanbul Officers’ Club are examined based on Reyner Banham principles to shed light on this localization in architecture. This study aims to provide an intercontinental case study of the integration of the expansion of global currents with cultural diversity. In this context, this study examines how Brutalism has been localized in Turkey and aims to expose unique examples that have yet to appear in the relevant literature.